2020
DOI: 10.7150/thno.45158
|View full text |Cite
|
Sign up to set email alerts
|

LXR activation potentiates sorafenib sensitivity in HCC by activating microRNA-378a transcription

Abstract: Sorafenib resistance is a major obstacle to the treatment of advanced hepatocellular carcinoma (HCC). MicroRNAs (miRNAs) are multifunctional regulators of gene expression with profound impact for human disease. Therefore, better understanding of the biological mechanisms of abnormally expressed miRNAs is critical to discovering novel, promising therapeutic targets for HCC treatment. This study aimed to investigate the role of miR-378a-3p in the sorafenib resistance of HCC and elucidate the underlying molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 46 publications
0
44
1
Order By: Relevance
“…The low level of miR-378a-3p is demonstrated in sorafenib-resistant cells. While, overexpression of this miRNA reversed sorafenib sensitivity in HCC sorafenib-resistant cells [ 241 ]. Taken together, the results suggest that downregulation of miRNA leads to overexpression of the IGF-1R gene and triggers sorafenib resistance in HCC cells.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%
“…The low level of miR-378a-3p is demonstrated in sorafenib-resistant cells. While, overexpression of this miRNA reversed sorafenib sensitivity in HCC sorafenib-resistant cells [ 241 ]. Taken together, the results suggest that downregulation of miRNA leads to overexpression of the IGF-1R gene and triggers sorafenib resistance in HCC cells.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%
“…Notably, excluding the let-7 family members, miR-378 ranked the 1 st among the rest of differentially expressed miRNAs in the liver of hypothyroid mice after T3 injection, indicating that miR-378 might be crucial for the regulatory role of TH (Figure 1 A and Figure S1 A). As miR-378 has been implicated in multiple metabolic processes 25 - 29 , we then chose miR-378 for further investigation. First of all, the expression of hepatic miR-378 was examined in the liver of mice under different thyroid status.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the molecular mechanisms of sorafenib resistance may provide novel therapeutic targets and more insights for combination therapies for the management of HCC. Although multiple studies have demonstrated possible mechanisms underlying sorafenib resistance, 24 , 25 , 39 , 40 the role of metabolic reprogramming and redox homeostasis in the process of sorafenib resistance has remained unknown.…”
Section: Discussionmentioning
confidence: 99%